EKSPLORASI KEANEKARAGAMAN MAKROBENTHOS DI DESA LAIKANG KABUPATEN TAKALAR, SULAWESI SELATAN - Arfan, Amal; Sanusi, Wahidah; Rakib, Muhammad (Jurnal Environmental Science, 2024)
This study aims to evaluate the distribution of macrobenthos in Laikang Village, Takalar Regency, South Sulawesi, and understand the environmental factors influencing it. The research was conducted through field surveys at three different observation stations, namely Station 1, Station 2, and Station 3, by counting the number of macrobenthos individuals at each station. Data analysis techniques included descriptive analysis for the composition and abundance of macrobenthos, as well as environmental analysis for factors affecting macrobenthos distribution, such as substrate type, water depth and temperature, water quality, nutrient availability, and species interactions. The results showed that Station 1 had the highest number of macrobenthos (123 individuals), followed by Station 2 (102 individuals) and Station 3 (77 individuals). Significant environmental factors influencing macrobenthos distribution included substrate type, water depth and temperature, water quality, nutrient availability, and interactions such as competition, predation, and symbiosis with other species. These findings indicate that macrobenthos play an important role as indicators of aquatic ecosystem health and provide insights into the composition and distribution of macrobenthos in the study area. This research has significant implications for understanding ecosystem balance. Active community participation in the conservation of macrobenthos and environmental management is expected to maintain ecosystem sustainability and improve the welfare of coastal communities.